A post-revanchist city: A governmentality perspective on public participation in Nanjing, China. (March 2022) - Cao, Liu
Abstract: Even though a new urban policy (public participation) that seeks to avoid the criticisms of radical urban regeneration has now been widely applied in Nanjing, China, the alleged success of this urban policy is questionable. While recent research has given greater attention to growing discussions of participatory approaches of Chinese urban regeneration projects, a majority of existing literature has only examined the nature or limitations of public participation, there has been far less consideration of the government's motivation in delivering these inclusive policies. This paper interprets Nanjing's inclusive urban policies through the conceptual lens of governmentality by analyzing the revanchist residual of Chinese urban regeneration. This research combines narratives from in-depth interviews (with a particular focus on key policymakers) and supplementary data from policies and archival records. It demonstrates that the implementation of inclusive urban policies in Nanjing is a remedy to the past "revanchist" urban regeneration policies. Indeed, public participation is a method refers to the restoration of residents' rights, seeking to direct them to behave towards what the government wants them to be. To that end, I conclude that if the spirit of revanchism still exists, it is through the inclusive urban policies to conduct local residents' conducts. Highlights: Public participation has become an evident feature in response to previous revanchist urban regeneration strategies. Public participation virtually is the method to restore local residents' rights during urban regeneration processes. Though public participation has been delivered, negative gentrification impacts are still impacting local residents. If the spirits of revanchism still exists, it is through the inclusive urban policy to conduct local residents' conducts.